Proceso de Conciliación de los Bienes Institucionales de la UTB - Muñoz Miranda, Kevin Javier (2018)
The Technical University of Babahoyo is the entity in which the problem is generated that will be announced, which is a higher education institution that was created through Decree # 1508 of October 5, 1971, and, promulgated in Official Gazette # 327 of 8 October of the same year, has legal status, and is governed by the Constitution of the Republic of Ecuador, the Organic Law of Higher Education and its General Regulations, the rest laws of the Republic, norms issued by the CES, CEAACES, and their respective relevant regulations. (Superior, Council of Higher Education, 2015) The Department of Property and Inventory Control fulfills the specific function of the income, shelter and control of the goods that are distributed in the different dependencies of the Technical University of Babahoyo. Likewise, the Administrative Financial Department, which is derived in three areas, Accounting, Public Purchases, Treasury; the same ones that are in charge of the timely registration of all the activities that generate an economic event in the institution.